Imaging of female pelvic malignancies regarding MRI, CT, and PET/CT: part 2 = Bildgebung weiblicher Beckentumoren unter Berücksichtigung von MRT, CT und PET/CT - Alt, Céline D.; Brocker, Kerstin A.; Eichbaum, Michael H. R.; Sohn, Christof; Arnegger, Florian U.; Kauczor, Hans-Ulrich; Hallscheidt, Peter (Strahlentherapie und Onkologie, 2011)
Purpose: To compose diagnostic standard operating procedures for both clinical and imaging assessment for vulvar and vaginal cancer, for vaginal sarcoma, and for ovarian cancer. Methods: The literature was reviewed for diagnosing the above mentioned malignancies in the female pelvis. Special focus herein lies in tumor representation in MRI, followed by the evaluation of CT and PET/CT for this topic. Conclusion: MRI is a useful additional diagnostic complement but by no means replaces established methods of gynecologic diagnostics and ultrasound. In fact, MRI is only implemented in the guidelines for vulvar cancer. According to the current literature, CT is still the cross-sectional imaging modality of choice for evaluating ovarian cancer. PET/CT appears to have advantages for staging and follow-up in sarcomas and cancers of the ovaries.
Gesehen am 01.03.2022